Composite materials : mechanics, manufacturing and modeling - Sharma, Sumit, 1985- (Boca Raton : CRC Press, 2021)
Composite materials find diverse applications in areas including aerospace, automotive, architecture, energy, marine and military. This comprehensive textbook discusses three important aspects including manufacturing, mechanics and dynamic mechanical analysis of composites. The textbook comprehensively presents fundamental concepts of composites, manufacturing techniques and advanced topics including as advances in composite materials in various fields, viscoelastic behavior of composites, toughness of composites and Nano mechanics of composites in a single volume. Topics such as polymer matrix composites, metal matrix composites, ceramic matrix composites, micromechanical behavior of a lamina, micromechanics and nanomechanics are discussed in detail. Aimed at senior undergraduate and graduate students for a course on composite materials in the fields of mechanical engineering, automobile engineering and electronics engineering, this book: Discusses mechanics and manufacturing techniques of composite materials in a single volume. Explains viscoelastic behavior of composites in a comprehensive manner. Covers fatigue, creep and effect of thermal stresses on composites. Discusses concepts including bending, buckling and vibration of laminated plates in detail. Explains dynamic mechanical analysis (DMA) of composites.
OCLC-licensed vendor bibliographic record.
Keywords: Composite materials; SCIENCE / Mechanics / General; TECHNOLOGY / Engineering / Mechanical; TECHNOLOGY / Material Science